The Administrative Leadership effect in empowering the nonprofit Organizations employees in applying to the Ministry of Endowments and Islamic affairs in state of Qatar - Salem, Mamoun Youssef (Journal of Economic, Administrative and Legal Sciences, 2018)
The research aims to Identify the effect of administrative leadership in empowerment at the employees in the Ministry of Awqaf and Islamic Affairs as Governmental nonprofit Organization. It also aimed to detect whether there are significant differences in the responses of the workers at the role/effect of the leadership in implementing empowerment on them due to the personal and functional variables; In order to achieve that, the researcher built a Questionnaire, The research population consist of all staff in major Five Departments in the Ministry, however the study sample was (375)employee (male & female); The research depends on descriptive analytical method; The data were collected through this questionnaire created and developed to measure the objectives of the research and to examine its hypotheses.Then the data were analyzed by (SPSS) program; The researcher reached to the following findings: There is a significant role/effect for the Managerial Leader ship in the improvement of Organizational Behavior& capabilities to the employees. There is a significant role/effect for the Managerial Leader ship in the Empowerment of the employees regardless of their age, sex, past experience, position and qualifications. There is a significant role/effect for the Managerial Leader ship in Fulfilling the essential needs to the employees. The researcher recommendthe following: It’s important to establish mutual trust between the employer and the employees in the Ministry It’s important to encourage self- managed work groups in the ministry.